Instructional delivery system of the Bicol University Regional Institute of Fisheries Technology program an evaluation - Cano, Josefina Barnedo (1987)
The study looked into the various adaptation mechanisms and changes in the B.U. Regional Institute of Fisheries Technology program from school year 1983-1984 to 1985-1986 in terms of its effectiveness in carrying out objectives. The study covers the organizational set-up, the instructional system and the physical facilities such as buildings, equipment, books and other services of the BU-RIFT. The study hopes that it can make some contributions in the field of fishery education.
Thesis (Ph.D.)--University of the Philippines, Diliman.
Typescript.
Keywords: Bicol University -- Regional Institute of Fisheries Technology; Fishery schools; Fishery technology